Influence of school environment in the teaching and learning of physical education - Muhamad Zahıdı; Rahmad Samad; Syed Kamaruzaman Bin Syed Alı (Türk Spor ve Egzersiz Dergisi)
This study discusses the level of constraint factors in school environment in the implementation of the teaching of Physical Education in primary schools. To determine the level of factors, this study employed survey method on 310 respondents who teach Physical Education for Year 6 pupils in Perak, Malaysia. The collected data has been analysed by utilising descriptive statistics developed with SPSS version 13.0. Based on the findings, generally all statements showed high mean values of between 4.17 and 4.55. The statement that implied unsafe field conditions showed the highest mean value of M=4.55, SD=0.886. While, the statement that implied unpredictable weather condition during Physical Education showed the lowest mean value of M=4.17, SD=1.109. As implication, the teaching and learning of Physical Education cannot be implemented effectively. Conclusively, the constraint factors in school environment have direct relationship with the field condition, Physical Education equipments, funding and administration system.